2021
DOI: 10.3390/ijms22136758
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Methacrylated Gelatin and Hyaluronic Acid Hydrogel Scaffolds. Preparation and Systematic Characterization for Prospective Tissue Engineering Applications

Abstract: Hyaluronic acid (HA) and gelatin (Gel) are major components of the extracellular matrix of different tissues, and thus are largely appealing for the construction of hybrid hydrogels to combine the favorable characteristics of each biopolymer, such as the gel adhesiveness of Gel and the better mechanical strength of HA, respectively. However, despite previous studies conducted so far, the relationship between composition and scaffold structure and physico-chemical properties has not been completely and systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 71 publications
3
80
0
Order By: Relevance
“…SEM images confirmed that an increase in the HA weight percentage in the scaffolds gives rise to more rugged void walls for the hybrid 3% HCS-2% HHA scaffold than those observed for the hybrid 3% HCS-1% HHA hydrogel, that is, a very porous structure but with more disorganized pores of mean sizes of ca. 30 μm is still retained ( Figure 4 G), in agreement with the structure observed in other hybrid hydrogel scaffolds containing HA ( Chang et al., 2013 ; Gilarska et al., 2018 ; Velasco- Rodriguez et al., 2021 ). Conversely, the use of LHA in the scaffold composition does not seem to have a great impact on the scaffold structure.…”
Section: Resultssupporting
confidence: 88%
“…SEM images confirmed that an increase in the HA weight percentage in the scaffolds gives rise to more rugged void walls for the hybrid 3% HCS-2% HHA scaffold than those observed for the hybrid 3% HCS-1% HHA hydrogel, that is, a very porous structure but with more disorganized pores of mean sizes of ca. 30 μm is still retained ( Figure 4 G), in agreement with the structure observed in other hybrid hydrogel scaffolds containing HA ( Chang et al., 2013 ; Gilarska et al., 2018 ; Velasco- Rodriguez et al., 2021 ). Conversely, the use of LHA in the scaffold composition does not seem to have a great impact on the scaffold structure.…”
Section: Resultssupporting
confidence: 88%
“…Therefore, it can be concluded that the combination of the two hydrophilic polymers results in lower thermal stability, which is slightly improved by crosslinking one of the polymers, that being gelatin in this study. Thermal stability would be significantly improved by modifying HA, using thiolation or methacrylation [32,33].…”
Section: Thermal Stability Of Each Scaffoldmentioning
confidence: 99%
“…At the same time, the Young's modulus of 15% GelMA is about 10 ​kPa [ 26 ], and its mechanical properties are weaker than those of native skin tissues [ 27 ]. To overcome this limitation, hybrid GelMA/HAMA hydrogels were fabricated, demonstrating improved physical properties [ 28 ]. Furthermore, in mixed GelMA hydrogels, 5% HAMA showed increased mechanical strength compared to 1% HAMA [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…To overcome this limitation, hybrid GelMA/HAMA hydrogels were fabricated, demonstrating improved physical properties [ 28 ]. Furthermore, in mixed GelMA hydrogels, 5% HAMA showed increased mechanical strength compared to 1% HAMA [ 28 ]. Therefore, in subsequent experiments, 15% GelMA and 5% HAMA were used.…”
Section: Resultsmentioning
confidence: 99%